Corporate Tax Aggressiveness in IDX Retail Firms: Effects of Profitability, Capital, Inventory, Sales Growth, and CSR - Asabrina Sri Tesalonika Duha; Etty Herijawati (PEARL, 2025)
This study investigates the influence of Profitability, Capital Intensity, Inventory Intensity, Sales Growth, and Corporate Social Responsibility (CSR) on Tax Aggressiveness among retail subsector firms listed on the Indonesia Stock Exchange (IDX) over the period 2019–2023. A total of 10 retail companies were selected as the research sample, with data obtained from audited annual financial reports published during the study period. The research adopts a quantitative approach using multiple linear regression analysis to examine both partial and simultaneous effects of the independent variables on tax aggressiveness. The findings reveal that Profitability has a positive and statistically significant impact on tax aggressiveness, indicating that more profitable firms are more likely to engage in tax avoidance strategies. In contrast, Capital Intensity, Inventory Intensity, and CSR do not exhibit significant effects, suggesting these factors are less influential in shaping tax planning behavior. Sales Growth, however, shows a significant positive effect, implying that firms with higher sales growth are more inclined toward tax aggressiveness. Simultaneously, all independent variables collectively exert a significant effect on tax aggressiveness. These results contribute to the literature on corporate tax behavior and may serve as input for fiscal policymakers, investors, and academics in identifying key determinants of tax planning within the retail sector in emerging markets.